MIR506 induces autophagy-related cell death in pancreatic cancer cells by targeting the STAT3 pathway. Issue 4 (3rd April 2017) - Sun, Longhao; Hu, Limei; Cogdell, David; Lu, Li; Gao, Chao; Tian, Weijun; Zhang, Zhixiang; Kang, Ya'an; Fleming, Jason B.; Zhang, Wei
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive and lethal cancer. The role of autophagy in the pathobiology of PDAC is intricate, with opposing functions manifested in different cellular contexts. MIR506 functions as a tumor suppressor in many cancer types through the regulation of multiple pathways. In this study, we hypothesized that MIR506 exerted a tumor suppression function in PDAC by inducing autophagy-related cell death. Our results provided evidence that downregulation of MIR506 expression was associated with disease progression in human PDAC. MIR506 triggered autophagic flux in PDAC cells, which led to autophagy-related cell death through direct targeting of the STAT3 (signal transducer and activator of transcription 3)- BCL2-BECN1 axis. Silencing and inhibiting STAT3 recapitulated the effects of MIR506, whereas forced expression of STAT3 abrogated the effects of MIR506 . We propose that the apoptosis-inhibitory protein BCL2, which also inhibits induction of autophagy by blocking BECN1, was inhibited by MIR506 through targeting STAT3, thus augmenting BECN1 and promoting autophagy-related cell death. Silencing BECN1 and overexpression of BCL2 abrogated the effects of MIR506 . These findings expand the known mechanisms of MIR506 -mediated tumor suppression to activation of autophagy-related cell death and suggest a strategy for using MIR506 as an anti-STAT3 approach to PDAC treatment.